Assembly Sequence Planning for Rectangular Modular Robots with Accessibility Constraints - Anelize Zomkowski Salvi; Henrique Simas (Journal of Robotics)
Product assembly is the final step in a manufacturing process where the individual components of a product are joined together. Assembly sequence planning (ASP) can be defined as the problem of finding a collision-free sequence of operations that allow the product assembly. Considering that during assembly individual modules cannot pass through a gap only as large as a module side, the ASP problem can be extended to modular robots, more specifically to rectangular modular robots. The main ASPs presented in the literature that are applicable to rectangular modules do not allow configurations with narrow corridors, i.e., corridors which are too narrow for a robot to transverse. Furthermore, these ASPs do not allow preassembled substructures or the free selection of the assembly starting point. Thus, the main goal of this work is to extend the classes of rectangular modular robot configurations that can be assembled without violating the accessibility condition. This paper introduces three novel ASP for constructing planar target structures composed of rectangular modular robots. Each ASP is adequate for a different scenario. Original implementation results and mathematical proofs for the three novel ASPs are also presented. To the best of the authors’ knowledge, this is the first work that presents, considering the accessibility condition, how to obtain centralized ASPs for assembling planar structures composed of rectangular modules with narrow corridors. Furthermore, the novel ASPs allow structures composed of subsets of preassembled modules and configurations with internal holes. They also allow the choice of the assembly starting point. Moreover, the third ASP proposed in this work allows achieving discontinuous assembly paths, i.e., wherever possible, the ASP allows a novel module to not connect to the latest added robot.